Motivation Improvement and Geography Learning Results Through Inquiry Based Learning Model to Class X-A Students at SMA Frater Makassar - Tirangka, Matius; Maddatuang, Maddatuang; Nyompa, Sukri (UNM Geographic Journal, 2017)
The research aims to discover (1) the students’ learning motivation in Geography at SMA Frater Makassar, (2) the description of Geography learning results at SMA Frater Makassar, (3) the relation between the use of inquiry based learning model on the improvement of the students’ learning motivations at SMA Frater Makassar, (4) the relation between the use of inquiry based learning model on the improvement of the students’ learning results at SMA Frater Makassar. The data were collected by using observation method about the students and teachers’ activities and learning result test in each of learning cycle. The data were analyzed by using descriptive statistics analysis technique. The results of the research reveal that (1) the students’ learning motivation in Geography learning seemed to be excited, innovative, and creative in asking questions, (2) the descripton of Geography learning results in cycle I, the students’ learning results who reached classical completeness is 69 percent and in cycle II increase to 86 percent, (3) the relation of the use of inquiry based learning model, there is relation between learning model and the students’ learning motivation where inquiry based learning model emphasized more in group discussion, (4) the relation of the use of inquiry based learning model was seen in students and teachers’ activities on inquiry based learning model shows improvement.